Synthesis and catalytic performance of Au-CeO₂ nanocomposites for the reduction of para-nitrophenol - Azmi, Nur Adlina (2025)
Gold (Au) nanoparticles supported on cerium oxide (CeO2) have shown promising catalytic performance for environmental applications, particularly in the reduction of p-nitrophenol (p-NP). Among various synthesis approaches, deposition precipitation (DP) and reduction-deposition (RD) are widely used for anchoring Au nanoparticles onto CeO2. However, achieving well-dispersed, stable Au nanoparticles with high catalytic efficiency remains a significant challenge. Furthermore, there is a lack of comparative studies evaluating the effectiveness of these methods in p-NP reduction, creating uncertainty about their relative performance. This study aims to compare the catalytic performance of Au-CeO2 nanocomposites synthesized via DP and RD methods, using p-NP reduction as a model reaction. CeO2 was first synthesized through chemical precipitation, followed by Au nanoparticles immobilization using DP and RD techniques. In the RD method, two different reducing agents were employed: sodium borohydride (strong reducing agent, RD1) and sodium citrate (weak reducing agent, RD2). The effect of catalyst dosage (1-10 mg) and p-NP concentration (0.05-0.20mM) on catalytic activity was systematically investigated. Fourier Transform Infrared (FTIR) spectroscopy confirmed successful Au immobilization through characteristic peak shifts from 520 cm-1 (CeO2 support) to 500 cm-1 (DP), 508 cm- 1 (RD1) and 501 cm-1 (RD2). This peak corresponds to O-Ce-O bond. The peaks in the range of 3300–2800 cm-1, corresponding to O-H stretching in CeO₂. All Au- CeO2 catalysts achieved 100% conversion of p-NP to p-aminophenol. The calculated rate constant (k) was 2.17 x 10-3 s-1 (DP), 2.15 × 10−3 s⁻¹ (RD1), and 8.59 x 10-4 s-1 (RD2). Therefore, the DP method is the best method because it shows the highest rate constant, indicating the fastest reaction. Although all methods achieved 100% conversion, DP provides the most efficient catalytic activity. These findings highlight the importance of the synthesis method and reducing agent in optimizing the activity of Au-CeO2 catalyts.